2019
DOI: 10.1115/1.4045388
|View full text |Cite
|
Sign up to set email alerts
|

Flexure Pivot Oscillator With Intrinsically Tuned Isochronism

Abstract: The most important property for accurate mechanical time bases is isochronism: the independence of period from oscillation amplitude. This paper develops a new concept in isochronism adjustment for flexure-based watch oscillators. Flexure pivot oscillators, which would advantageously replace the traditional balance wheel-spiral spring oscillator used in mechanical watches due to their significantly lower friction, exhibit nonlinear elastic properties that introduce an isochronism defect. Rather than minimizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…In our previous research on flexure oscillators, we developed design principles that allow to minimize gravity effects [15,22] and introduced the concept of isochronism tuning by changing second order stiffness properties of the oscillator [16]. We showed that we could compensate isochronism defects by adjusting the stiffness of flexures whose motion is of second order of the main oscillation, that is, the same order as the isochronism defect, see Eq.…”
Section: State Of the Artmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous research on flexure oscillators, we developed design principles that allow to minimize gravity effects [15,22] and introduced the concept of isochronism tuning by changing second order stiffness properties of the oscillator [16]. We showed that we could compensate isochronism defects by adjusting the stiffness of flexures whose motion is of second order of the main oscillation, that is, the same order as the isochronism defect, see Eq.…”
Section: State Of the Artmentioning
confidence: 99%
“…(6). The fact that this is is done by changing oscillator properties without affecting any other crucial characteristic of the pivot (such as such as nominal stiffness, gravity sensitivity and parasitic center shift) is called intrinsic isochronism tuning [16] and is superior to existing solutions. Indeed, the first flexure pivot oscillator to be introduced in a watch, the 2014 "Genequand System" [9,10] used an external mechanism to tune its isochronism [23]; other oscillators based on the crossed flexure pivot [24] use special values for the point at which the leaf springs cross and the angle between them to reach isochronism [22,25,26,27,28] which, however, does not qualify as isochronism tuning since changing these parameters affects other crucial properties of the pivot [16,22,29,30].…”
Section: State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations